Centro de resocialización penitenciaria de delitos menores (2021)
In Bogotá as in Colombia, there are problems in the prisons of infrastructure, time of execution of works, overcrowding, lack of spaces for the effective re-socialization of this population. It is a critical state, the living conditions of the prison population within the penitentiary establishments, due to overcrowding, hygiene, social environment, ineffective spaces where a sentence is served for a certain time, generating problems among inmates, either psychological, verbal, physical and in their process of reflection and re-socialization.